Severe hypoglycemia exacerbates myocardial dysfunction and metabolic remodeling in diabetic mice. (1st March 2020) - Huang, Lishan; Zhou, Yu; Chen, Zhou; Zhang, Meilian; Zhan, Zhidong; Wang, Linxi; Liu, Libin
Abstract: Although several studies have revealed that adverse cardiovascular events in diabetic patients are closely associated with severe hypoglycemia (SH), the causal relationship and related mechanisms remain unclear. This study aims to investigate whether SH promotes myocardial injury and further explores the potential mechanisms with focus on disturbances in lipid metabolism. SH promoted myocardial dysfunction and structural disorders in the diabetic mice but not in the controls. SH also enhanced the production of myocardial proinflammatory cytokines and oxidative stress. Moreover, myocardial lipid deposition developed in diabetic mice after SH, which was closely related to myocardial dysfunction and the inflammatory response. We further found that myocardial metabolic remodeling was associated with changes in PPAR-β/δ and its target molecules in diabetic mice exposed to SH. These findings demonstrate that SH exacerbates myocardial dysfunction and the inflammatory response in diabetic mice, which may be induced by myocardial metabolic remodeling via PPAR-β/δ. Highlights: Severe hypoglycemia was successfully induced in type 1 diabetic (T1DM) mice. Severe hypoglycemia worsens myocardial dysfunction and structural disorder. Severe hypoglycemia induced PPAR-β/δ–related metabolic remodeling in T1DM mice.